The Role Played by Folklore in Raising up an African Child - Nontokozo Gladys Mdhluli (Journal of Education and Learning Technology)
Folklore is commonly understood to be a collection of traditional beliefs, traditions, and practices that are practiced by communities all over the world. It is essential to pass down social standards and cultural values from generation to the next. The purpose of this study is to investigate how folklore, especially in African civilizations, shapes moral behavior, social values, and collective identity. Additionally, the study explores how folklore serves as a vehicle for communal cohesiveness, education, and amusement. A qualitative study methodology was used, which included interviews with elderly and cultural practitioners in addition to content analysis of a few chosen folktales, legends, proverbs, and songs. The results show that folklore is still an effective means of fostering the community, resolving conflicts, and imparting moral lessons. In addition to providing pleasure, stories read by the fire in the evening also encourage proper behavior by imparting moral lessons. Although they are frequently disregarded in contemporary settings, superstitions and irrational beliefs have traditionally assisted societies in overcoming adversity and uncertainty. Because it promotes intergenerational communication and conserves indigenous knowledge, the conversation highlights the timeless value of folklore even in modern culture. It also recommends more research and documentation of oral traditions to preserve them for upcoming generations. This study adds to the body of knowledge by demonstrating the diverse functions of folklore in society, not only as a holdover from the past, but as a dynamic, ever-evolving mode of cultural expression that still shapes ethics, behaviour, and identity formation.